2010
DOI: 10.1111/j.1752-699x.2010.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary pleural epithelioid hemangioendothelioma (EHE) – two cases and review of the literature

Abstract: Introduction: We present two cases with symptoms of progressively worsening cough, dyspnea, decreased exercise tolerance and right-sided back pain in the first case and upper respiratory symptoms characterized by cough and a low grade fever in the second case. Methods: Report of two cases. Results:The initial chest X-ray in both the cases showed pleural effusion. Further imaging with computed tomography of the chest confirmed the effusion in both cases. Thoracentesis was done in both of them revealed an exudat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 18 publications
0
31
0
1
Order By: Relevance
“…Pleural EHE is rare, usually affects males, and is associated with a grim prognosis with disseminated disease [1][2][3]. Pleural involvement in females is even more unusual.…”
Section: Discussionmentioning
confidence: 95%
“…Pleural EHE is rare, usually affects males, and is associated with a grim prognosis with disseminated disease [1][2][3]. Pleural involvement in females is even more unusual.…”
Section: Discussionmentioning
confidence: 95%
“…Most commonly, bevacizumab is used in combination with paclitaxel. Regardless of the chemotherapy bevacizumab is paired with, progression-free survival (PFS) and OS varies from months to years [Grotz et al 2010;Lazarus et al 2011;Gaur et al 2012;Salech et al 2010]. A single-arm, multicenter, phase II trial utilizing single agent bevacizumab for unresectable EHE reported PFS and OS of 39 weeks and 143 weeks, respectively, when bevacizumab was given at 15 mg/kg every 3 weeks [Agulnik et al 2013].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, bevacizumab has been used with carboplatin, paclitaxel, docetaxel and/or etoposide [Grotz et al 2010;O'Grady, 2000;Lazarus et al 2011;Gaur et al 2012]. Most commonly, bevacizumab is used in combination with paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery remains the only curative option while most previously reported cases have failed to show a meaningful clinical response to radiotherapy and/or chemotherapy, suggesting resistance of this tumor to standard anticancer modalities [1,5]. The anti-vascular endothelial growth factor (anti-VEGF) monoclonal antibody bevacizumab has also been used with variable outcomes in a limited number of selected cases [6][7][8][9][10][11]; therefore, the therapeutic benefit of this agent in EH remains controversial. We herein report a case series of four patients with EH, including two cases of localized lung and pleural EH and two cases of liver and bone EH with pulmonary metastases, which were all treated with bevacizumab in the Oncology Unit GPP, "Sotiria" General Hospital, University of Athens, and briefly review the relevant literature (Table 1).…”
Section: Introductionmentioning
confidence: 96%